The effect of a sealant on the microleakage of composite resin restorations: an in vivo study - (:unkn) unknown (My University, 1992)
The aim of this study was to evaluate the effect of sealant application in reducing microleakage of the composite resin restorations under in vivo conditions. Occlusal composite resin restorations were made in 24 caries-free primary molars which were about to exfoliate, in children aged between 10 and 13 years. Of these restorations, 12 were sealed with a fissure sealant whereas the others were kept unsealed as controls. After 1 month, the teeth were extracted and immersed in a 2% methylene blue dye solution. The dye penetration alongside the restorations was evaluated using a stereo-microscope. The findings indicated that sealant application significantly (p < 0.05) reduced the microleakage of composite restorations but did not eliminate it completely.
Keywords: Humans; Adolescent; Child; Composite Resins; Dental Leakage; Dental Restoration, Permanent; Glass Ionomer Cements; Pit and Fissure Sealants